2021
DOI: 10.21608/mid.2021.92720.1187
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mex AB-Opr M efflux pump system and meropenem resistance in Pseudomonas aeruginosa isolated from surgical intensive care unit

Abstract: Background: Meropenem resistance of Pseudomonas aeruginosa (P. aeruginosa) is considered an increasing problem. Efflux pump is one of multiple mechanisms that are responsible for this resistance. This study aimed to phenotypically and genotypically detect prevalence of efflux pump mediated meropenem resistance among P. aeruginosa isolates. Methods: Pseudomonas aeruginosa was isolated from different clinical specimens and identified by conventional methods and confirmed by Viètek MS Malditof Mass Spectroscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…This study aimed to detect the association between the presence of MexA/MexB genes and the resistance pattern among P. aeruginosa isolates from Ain Shams University hospitals A total of 60 isolates of P. aeruginosa were included in this study, most of isolates were isolated from urine samples 26 (43.3%), followed by sputum samples 14 (23.3%), 12 (20%) isolates were isolated from pus samples, four (6.7%) were isolated from CSF, two (3.3%) were isolated from central lines and two (3.3%) were isolated from blood. This finding goes in accordance with a study conducted in Egypt by Abdallah et al [13] who reported that the most of P. aeruginosa were isolated from endotracheal samples (44%) followed by urine (36%) and the least from blood (2%). Also, Mohamed et al [14] reported higher rate from respiratory samples (29%) followed by urine (27%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study aimed to detect the association between the presence of MexA/MexB genes and the resistance pattern among P. aeruginosa isolates from Ain Shams University hospitals A total of 60 isolates of P. aeruginosa were included in this study, most of isolates were isolated from urine samples 26 (43.3%), followed by sputum samples 14 (23.3%), 12 (20%) isolates were isolated from pus samples, four (6.7%) were isolated from CSF, two (3.3%) were isolated from central lines and two (3.3%) were isolated from blood. This finding goes in accordance with a study conducted in Egypt by Abdallah et al [13] who reported that the most of P. aeruginosa were isolated from endotracheal samples (44%) followed by urine (36%) and the least from blood (2%). Also, Mohamed et al [14] reported higher rate from respiratory samples (29%) followed by urine (27%).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Abdallah et al [13] stated that out of 35 meropenem resistant isolates, MexA gene was detected in 54.2% while MexB gene was detected in 51.4% and both genes were detected in 40%. Another study done by Murugan et al [22] detected higher frequency of efflux pump genes among tested isolates where (51%) for MexA and (46.5%) for MexB, and (40.5%) for Opr M.gene.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The results of the current study showed that 15 isolates (93.75 %) of the tested study isolates possess the mexA gene, and thus our results are in agreement with the findings of Ugwuanyi and his group (2020) as the mexA gene was 90% present, while the presence of the mexA gene was close to As reached by Al-Grawi and his group (2012), Tomas and his group (2010), Abbas and his group (2018), where the percentages were 100%, 88.2%, 100%, respectively. While the percentage of the gene's presence contradicted what was reached (Al-Obaidi, 2015) in his study, where the percentage reached by it was (68.8%), as well as what was reached by Abdallah et al, (2021), where the percentage of the gene was 54%. While the presence of the oprM gene was revealed, and after the electrophoresis, it was observed that one bundle appeared in the pits at the same required level after exposing the gel to ultraviolet rays, evidence of the link of the initiator with its complementary sequence on the binding of the template DNA, when comparing the duplicated bundles with the volumetric guide with The known beam sizes are as shown in Figure (2).…”
Section: Resultsmentioning
confidence: 57%
“…A study done byAdabi et al, (2015) they observed that all P. aeruginosa isolates which isolated from burn patients were resistance to ciprofloxacin due to have both MexA and MexC genes. Another recent work done byAbdallah et al, (2021) they recorded that the number and rate of P. aeruginosa isolates obtained from different clinical sources were 78(29.4%) and all isolates of P. aeruginosa that harbored efflux pump genes of MexA, MexB and OprM were high resistance to drug of meropenem. A study done by…”
mentioning
confidence: 98%